PERBANDINGAN IBNU HAJAR DENGAN AL-’AINI DALAM MEN-SYARAH SHAHIH AL-BUKHARI - Ridha, Muhammad (Alhurriyah, 2011)
Hadiths are teaching source of islamic law after the Qur’an, because the Hadiths of Rasulullah explained everything that exist in the Qur’an. One of the Hadith that often discussed by the Muslim theologian is Bukhari’s shaheeh hadith book. Here will explain how the Muslim theologian do Shari’a with Bukhari’s shaheeh.